Branding Strategy for Romania as a Tourist Destination - Cosma, Smaranda; Pop, Cornelia; Negrusa, Adina (Univerzita Pardubice, 2006)
In the last 2 years a lot of discussions took place regarding the fact that Romania has no brand – as a nation or a tourist destination. For now, no further actions were initiated to transpose the ideas resulted from those discussions into a project. The implementation of such a project remains a dream. This paper would try to present Romania’s competitive advantages and the branding strategy our country should have as a tourist destination.
Keywords: branding; Strategy; tourist destination; Romania